Study on Acute and Subchronic Toxicity, Cytotoxicity and In Vitro Developmental Toxicity of Safflower Extracts of “IL 111” and “LRV 51 51” Cultivars: Toxicity and teratogenicity of safflower - Mehran Mohseni; Mohammad Seyedabadi; Ebrahim Azizi; Seyed Mohammad Shariatpanahi; Hamidreza Monsef Esfahani; Manochehr Hamedi; Seyed Nasser Ostad (Iranian Journal of Pharmaceutical Sciences, 2012)
Toxic and direct teratogenic potential of two dominant Iranian cultivars of Carthamus tinctorius (safflower), floret extracts, IL 111 and LRV 51 51, were investigated. The extracts are commonly used in foods and medicinal products. Neither death nor alteration of stereotype activities was observed with IL 111 and LRV 51 51 extracts up to 17 g/kg in 48 h in mice and rats. Haemoglobin was decreased, prothrombin time was prolonged, serum TG, LDH, CPK and cholesterol was increased in rats which received IL 111 (1 g/kg) for 9 weeks (p<0.05). Comparatively, LRV 51 51 (1 g/kg) did not induce any change in haematological or biochemical factors. Histological examination of the liver, kidneys and spleen revealed some abnormalities with both extracts in the subchronic toxicity study. IL 111 and LRV 51 51 extracts elicited a dose dependent cytotoxicity in cultured balb/c (IC50: 394 and 429 μg/ml, respectively) and limb bud cells (IC50: 78 and 106 μg/ml, respectively). The total number of differentiated (stained) limb bud foci was also decreased when cells were exposed to either of C. tinctorius extracts (p<0.01). When the cytotoxicity was taken into account, the ratio of Alcian stained differentiated cells to the cytotoxicity was not significantly altered with any of the extracts, suggesting no remarkable level of teratogenicity.